Beyond decolonization: navigating the crisis of european art and history through amazonian Anthropology - Cova, Victor (Campos - Revista de Antropologia, 2025)
Experience, historical, aesthetic and ethnographic, as shifting grounds for knowledge often decried as mere belief, that is, as possibly invented or imagined, is a thread that runs through Peter Gow’s entire work. The point he was thereby trying to make had to do with what he considered to be the threat to anthropology’s raison d´´’être that had emerged with the so-called “crisis of representation” of the 1980s and only gained further ground thereafter until it had overtaken the entire discipline by the 2010s. Marxism and the 18th century were at the heart of what was being rejected by the post-moderns, and each because of the other. Crucially for Gow, what was being evacuated in the process was perhaps one of the most sophisticated product of both, and one foundational to Amazonian anthropology: Claude Levi-Strauss’s synthesis of pre-1950s anthropology (most prominently functionalism, diffusionism and boasian historicism) and a marxian sense of historical consciousness, anchored in a recognition of the crisis of the Enlightenment in modernity. This article attempts to shed a light on this obscure nexus (art, knowledge and history, Amazonia and Scotland, Marx and the 18th century, with Levi-Strauss at its heart) which increasingly preoccupied Peter Gow and can help both to understand his work and to understand how it might be furthered in and beyond Amazonia.